A comprehensive genome-wide analysis of long non-coding RNA and mRNA expression profiles of JAK2V617F-positive classical myeloproliferative neoplasms. Issue 2 (20th December 2021) - Zhou, Jie; Wu, Hao; Guo, Cheng; Li, Bing; Zhou, Li-Li; Liang, Ai-Bin; Fu, Jian-Fei
ABSTRACT: Aberrant expression of long non-coding RNAs (lncRNAs) is involved in the progression of myeloid neoplasms, but the role of lncRNAs in the JAK2V617F-positive subtype of classical myeloproliferative neoplasms (cMPNs) remains unclear. This study was conducted to clarify the expression and regulation patterns of lncRNAs in JAK2V617F-positive cMPNs, and to explore new potential carcinogenic factors of cMPNs. Bioinformatics analysis of microarray detection and wet testing verification were performed to study the expression and regulation signature of differentially expressed lncRNAs (DELs) and related genes (DEGs) in cMPNs. The expression of lncRNAs and mRNAs were observed to significantly dysregulated in JAK2V617F-positive cMPN patients compared with the normal controls. Co-expression analysis indicated that there were significant differences of the co-expression pattern of lncRNAs and mRNAs in JAK2V617F-positive cMPN patients compared to normal controls. GO and KEGG pathway analysis of DEGs and DELs showed the involvement of several pathways previously reported to regulate the pathogenesis of leukemia and cMPNs. Cis- and trans-regulation analysis of lncRNAs showed that ZNF141, DHX29, NOC2L, MAS1L, AFAP1L1, and CPN2 were significantly cis-regulated by lncRNA ENST00000356347, ENST00000456816, hsa-mir-449c, NR_026874, TCONS_00012136, uc003lqp.2, and ENST00000456816, respectively, and DELs were mostly correlated with transcription factors including CTBP2, SUZ12, REST, STAT2, and GATA4 to jointly regulate multiple target genes. In summary, expression profiles of lncRNAs and mRNAs were significantly altered in JAK2V617F-positive cMPNs, the relative signaling pathway, co-expression, cis- and trans-regulation were regulated by dysregulation of lncRNAs and several important genes, such as ITGB3, which may act as a promising carcinogenic factor, warrant further investigation.